1996
DOI: 10.1002/etc.5620150204
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and vertical distribution of total ammonia nitrogen and un‐ionized ammonia nitrogen in sediment pore water from the upper Mississippi River

Abstract: We examined the temporal and vertical distribution of total ammonia nitrogen (TAN) and un‐ionized ammonia nitrogen (NH3‐N) in sediment pore water and compared the temporal patterns of TAN and NH3‐N concentrations in overlying surface water with those in pore water. Pore water was obtained by core extraction and subsequent centrifugation. We measured TAN concentrations and calculated NH3‐N concentrations from February through October 1993 at four sites in Pool 8, upper Mississippi River, at depths of 0 to 4, 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…These differences were attributed to the higher pH in the over-2062 Environ. This vertical pH gradient is not an artifact of the laboratory exposure system because surface waters are often 0.4 to 1 pH unit greater than in pore water, although NH 3 -N concentrations in surface water are generally lower than in pore water [30]. Chem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences were attributed to the higher pH in the over-2062 Environ. This vertical pH gradient is not an artifact of the laboratory exposure system because surface waters are often 0.4 to 1 pH unit greater than in pore water, although NH 3 -N concentrations in surface water are generally lower than in pore water [30]. Chem.…”
Section: Discussionmentioning
confidence: 99%
“…First, sediment and water-only tests should be conducted to better characterize potential exposure routes for ammonia (and other contaminants) across life stages. Concentrations of ammonia in pore waters vary widely in river systems, with ranges of Ͻ1 to 10 mg TAN/L in the relatively uncontaminated upper Mississippi River [30] to Ͼ52 mg TAN/L in the grossly contaminated Fox River [40]. Although considerable research has been conducted on this relation in other aquatic species, relatively few data 2064 Environ.…”
Section: Discussionmentioning
confidence: 99%
“…. Frazier et al (1996) also found a wide range of concentrations (TAN: 0.7-4.0 mg l -1 ) in sediments of the lower portion of Navigation Pool 8. While there are concerns that ammonia toxicity contributes to large-scale declines in freshwater invertebrates (e.g., Sparks & Sandusky, 1981;Wilson et al, 1995), we found no published evidence that natural conditions in the UMR lead to toxic levels of unionized ammonia (NH 3 ).…”
Section: In Unenriched Waters Concentrations Of Nh 3 or Nhmentioning
confidence: 94%
“…Although some of these areas may contain lentic mussel species, populations may be sparse. Such areas could be less conducive to mussels because many are subject to anthropogenic sedimentation (McHenry et al, 1984), episodes of winter hypoxia (Bodensteiner & Lewis, 1992;Gent et al, 1995), high sediment ammonia (Frazier et al, 1996), or freeze to the bottom during winter in shallow areas (Gent et al, 1995).…”
Section: Factors Influencing Mussel Distributionsmentioning
confidence: 99%